ANZUS and Australia's Security: Australian Attitudes, October 1982 (ADA Dataverse, 2018)
Topics in this survey include: ANZUS; importance of ANZUS to Australia's security; types of defence co-operation between US and Australia; greater benefits gained by Australia from ANZUS; greater benefits gained by US from ANZUS; ANZUS and risk of attack of Australia; trust in US; maintaining ANZUS alliance; US v./ USSR in total military strength; US v./ USSR in naval strength; importance of US naval forces; visits by US warships carrying nuclear weapons; reasons for supporting/opposing visits by US warships. Standard variables include Federal voting intention, household size, age, marital status, schooling, occupation of respondent or of main income earner, household income, country of birth, industry sector, religion, tenure of dwelling, sex, area. This study is part of a series (SSDA No's 525 to 532) commissioned by the United States Information Service between 1982 and 1985 on Australians' attitudes to defence issues. Similar studies were carried out in New Zealand at the same time (SSDA No's 521 to 524) which contain some parallel questions.